EFEK EKSTRAK DAUN TEH (Camellia sinensis) KONSENTRASI 0,5% TERHADAP KADAR sIgA PADA SALIVA PENDERITA GINGIVITIS - Juni Handajani; Widya Asmara; Regina TC. Tandelilin (Faculty of Dentistry, Universitas Indonesia, 2015)
Enhanced humoral immune response (sIgA) can be caused by gingivitis. A study has been conducted on the effect of tea leaf extract (Camellia sinensis) at a concentration of 0,5% as mouth-wash on salivary sIgA level on gingivitis patients. Ten patients (age= 18-30 years) were divided into 2 groups so that five patients of the first group representes early gingivitis, and five patients of the second group represented normal gingiva. The gingival index by Loe and Silness (1963) was measured one day before treatment and five days after treatment. The first group was given tea leaf extract solution (0,5%) and the others were given aquabidest as control. Five ml of each solution was mouth washed for 5 seconds and this was repeated two times in the morning and at night before sleeping. All treatments were repeated for five days. Saliva samples were collected one day before treatment and five days after treatment. The sIgA level was measured using sIgA ELISA kit (Salimetrics LLC). Optical Density was read on standard plate at 450 nm. The results showed a significant decrease in the salivary sIgA level and in the severity of gingivitis by mouth-washing with a tea leaf extract at a concentration 0.5%.